(untitled) (TAJDID: Jurnal Ilmu Ushuluddin, 2024)
The issue of private parts, especially when related to men, is an issue that has reached an established level because it is rarely debated. This can be seen from the small number of studies that question this problem, which is of course different for women. At least the public has accepted that men have the obligation to cover the navel to the knees as awrah, without questioning and seeing the extent of the relevance of this limit in contemporary times. This research is a literature review that presents the hadith from Sunan Darul Qutni no. 771 as primary data with Maqashidi as the analytical tool. This research concludes that the understanding of the hadith by limiting men’s private parts to only the navel to the knees is no longer relevant in the current era. This is based on the argument that parts of the male body that are outside the established limits can in fact create sexual stimulation for the opposite sex or even members of the same sex, so there is a need to increase the limits of the private parts for men outside of the agreed provisions. This is to achieve the sharia objectives of hifz al-Nafs (protecting oneself), hifz nasl (protecting descendants) and hifz al-din (protecting religion).